Tirailleurs Sénégalais in Modern Hebrew Poetry: Nathan Alterman - Liora Bigon; Edna Langenthal (Humanities, 2023)
This article expands on a poem written by one of the central figures in modern Hebrew literature, Nathan Alterman (1910–1970), entitled “About a Senegalese Soldier” (1945). Providing the first English translation of this poem and its first (academic) discussion in any language, the article analyzes the poem against contemporary geopolitical, historical, and literary backgrounds. The article’s transdisciplinary approach brings together imperial and colonial studies, African studies, and (Hebrew) literature studies. This unexpected combination adds originality to mainstream postcolonial perspectives through which the agency of the Senegalese riflemen [Tirailleurs sénégalais] has been often discussed in scholarly research. By using a rich variety of primary and secondary sources, the article also contributes to a more elaborated interpretation of Alterman’s poetry. This is achieved through embedding the poem on the tirailleur in a tripartite geopolitical context: local (British Mandate Palestine/Eretz-Israel), regional (the Middle East), and international (France-West Africa). The cultural histories and literary traditions in question are not normally cross-referenced in the relevant research literature and are less obvious to the anglophone reader.